Calculation of Optimal Geometrical Magnification and Spatial Resolution of Betatron Tomograph; IOP Conference Series: Materials Science and Engineering; Vol. 189 : Modern Technologies for Non-Destructive Testing - Zhong Y. (2017, 2017)
Title screen